Infectious disease - Jaworski, C. A.; Donohue, B.; Kluetz, J. (Clinics in Sports Medicine, 2011)
Athletes are susceptible to the same infections as the general population. However, special considerations often need to be taken into account when dealing with an athlete who has contracted an infectious disease. Health care providers need to consider how even common illnesses can affect an athlete's performance, the communicability of the illness to team members, and precautions/contraindications related to athletic participation. Recent advances in the prevention, diagnosis, and/or management of frequently encountered illnesses, as well as certain conditions that warrant special attention in the athletic setting, are discussed in detail.